Prognostic Value of c-MET Expression in Patients With Pancreatic Cancer Receiving Adjuvant and Neoadjuvant Chemoradiation Therapy - Cuneo, Kyle C. (Int J Radiat Oncol Biol Phys, 2017)
PURPOSE: To determine the prognostic significance of c-MET expression and develop a predictor of distant failure in patients with resectable pancreatic cancer treated with chemoradiation. METHODS AND MATERIALS: We used a tissue microarray to study protein expression by immunohistochemistry in 102 patients treated surgically for pancreatic cancer. Two cores per patient were blindly scored from 0 (no staining) to 3 (strong staining) by a single pathologist. The Kaplan-Meier method was used to determine time to local and distant failure, overall survival, and progression-free survival. P values were calculated with the log–rank test. RESULTS: High tumor expression of c-MET was associated with a shorter time to distant failure in patients receiving neoadjuvant (n=23) or neoadjuvant therapy (n=73) (median 8.9 months vs 22.0 months, P=.0010). We then examined the ability of incorporating 2 known biomarkers, thymidylate synthase and DPC4 (SMAD4), with c-MET to risk-stratify patients. This multi-protein predictor divided our cohort into groups of similar numbers and was predictive of distant failure (median 13.4 months vs 24.2 months, P=.0094) but not of local control. CONCLUSION: c-MET is potentially predictive of distant failure. Using c-MET, DPC4, and thymidylate synthase, we developed a multi-protein predictor that could be used to risk-stratify patients and guide decisions regarding the sequencing of locoregional and systemic therapies in pancreatic cancer.